Positive Periodic Solutions for a Single-Species Model with Delay Weak Kernel and Cycle Mortality (Journal of Nonlinear Modeling and Analysis, 2024)
In this paper, by using the Krasnoselskii’s fixed-point theorem, westudy the existence of positive periodic solutions of the following single-speciesmodel with delay weak kernel and cycle mortality: $$x'(t) = rx(t)[1 − \frac{1}{K}\int^t_{−∞}αe^ {−α(t−s)} x(s)ds] − a(t)x(t),$$ and get the necessary conditions for the existence of positive periodic solutions.Finally, an example and numerical simulation are used to illustrate the validityof our results.